A Corpus-Based Study on the Pragmatic Use of the ba Construction in Early Childhood Mandarin Chinese - Tsung, Linda; Gong, Yang Frank (Frontiers in Psychology, 2021)
This article reports on an inquiry that investigated the development of ba constructions in early childhood Mandarin. All cases of ba construction were extracted from the Early Childhood Mandarin Corpus collected from 168 preschoolers aged 2;6, 3;6, 4;6, and 5;6 (year; month; Li and Tse, 2011). Early Childhood Mandarin Corpus, University of Hong Kong. Data analysis indicated that: (1) Mandarin-speaking children produced a repertoire of 11 types of ba construction, and the children in the youngest age group (age 2;6) were able to produce six types of them; (2) children at 4 years old (age 4;6) experienced a critical developmental period of pragmatic use, and at 5 years old (age 5;6) they had attained cognitive and linguistic maturity in understanding the semantic and syntactic features of ba constructions; and (3) there was a significant age effect on the production of three types of ba construction, but no significant association between the children’s gender and their production of ba constructions. These findings offer fresh insights into understanding Chinese children’s innate capacity to understand the co-occurrence constraints concerning the syntactic, semantic and verb features inherent in ba construction, and their developmental ability to denote telic events by resorting to the appropriate ba sentence patterns.